Transgressive Potential Prediction and Optimal Cross Design of Seed Protein Content in the Northeast China Soybean Population Based on Full Exploration of the QTL-Allele System - Feng, Weidan; Fu, Lianshun; Fu, Mengmeng; Sang, Ziqian; Wang, Yanping; Wang, Lei; Ren, Haixiang; Du, Weiguang; Hao, Xiaoshuai; Sun, Lei; Zhang, Jiaoping; Wang, Wubin; et al. (Frontiers in Plant Science, 2022)
Northeast China is a major soybean production region in China. A representative sample of the Northeast China soybean germplasm population (NECSGP) composed of 361 accessions was evaluated for their seed protein content (SPC) in Tieling, Northeast China. The SPC varied greatly with the mean SPC of 40.77%, ranging in 36.60-46.07%, but not as high as in the Chinese soybean landrace population with the mean SPC of 43.10%, ranging in 37.51-50.46%. The SPC increased slightly from 40.32~40.97% in the old maturity groups (MG, MGIII+II+I) to 40.93~41.58% in the new MGs (MG0+00+000). Using the restricted two-stage multi-locus GWAS (RTM-GWAS) with 15,501 SNP linkage-disequilibrium block (SNPLDB) markers, 73 SPC QTLs with 273 alleles were identified, explaining 71.70% of phenotypic variation, in which 28 QTLs were new ones. The evolutionary changes of QTL-allele structure from old MGs to new MGs were analyzed, and 97.79% alleles in new MGs were inherited from the old MGs with 2.21% new alleles emerged and 0.74% old alleles excluded. The small amount of new positive allele emergence without old negative allele exclusion plus possible recombination may well explain the slight SPC increase in the new MGs. The recombination potentials in SPC of all possible crosses were predicted with a mean of 43.29% (+2.52%) and maximum of 50.00% (+9.23%), and the maximum transgressive potential was 3.93%, indicating that SPC breeding potentials does exist in the NECSGP. A total of 120 candidate genes were annotated and functionally classified into 13 categories, indicating SPC is a complex trait conferred by a gene-network.